VATIS update : ozone layer protection. Vol. 4, No. 109, Nov-Dec 2011 - UN.ESCAP; Asian and Pacific Centre for Transfer of Technology (APCTT) (UN.ESCAP. Asian and Pacific Centre for Transfer of Technology, 2011)
VATIS Update Ozone Layer Protection is published 6 times a year to keep the readers up to date of most of the relevant and latest technological developments and events in the field of Ozone Layer Protection. The Update is tailored to policy-makers, industries and technology transfer intermediaries. Highlights : Data show significant Antarctic ozone hole -- Refrigerant helps convert solar heat into power -- Healthier, safer cylinder-cleaning solution -- Pentane process technology replaces CFC -- Water mist puts out fires at low pressure -- Non-fumigant alternatives for methyl bromide THE SCIENCE OF OZONE LAYER . 4 -- Data show evidence of significant Antarctic ozone hole -- Ozone hole closing, albeit slowly -- Ozone hole over the Arctic studied -- Cancer and cataract on the rise as ozone layer diminishes ODS PHASE-OUT IN INDIA . 6 -- National transition strategy for phase-out of CFCs in MDIs -- National Halon Banking Facility -- Duty exemption and discounts for non-ODS technology -- Essar Steel first beneficiary of IDBI Bank’s energy drive IN THE NEWS . 7 -- Twenty-four Asia-Pacific countries reach Goal Zero -- China launches ozone and climate change project -- Project in Malaysia to study ozone depletion by atmospheric halogen -- Philippines in preparation to phase out HCFCs -- Maldives at the forefront of environmental measures -- Three alternative refrigerants approved in the United States -- Indonesia to cut HCFC consumption by 10 per cent -- SolarChill largescale demo and technology transfer project -- New preferential tariffs in Viet Nam REFRIGERATION/AIR-CONDITIONING . 10 -- Hydrocarbon refrigerant replacement for R22 -- Natural refrigerant for transport refrigeration -- Refrigerant helps convert solar heat into power -- New semi-hermetic compressors -- High-efficiency automotive airconditioning refrigerant -- Chiller saves 50 per cent energy SOLVENTS . 12 -- Products to make oil fields cleaner and greener -- Heavy-duty degreaser certified as clean air solvent -- Hydrochlorofluoroolefin compositions -- ...